Boundary element analysis of cracks in composite laminates - Liu, Futai. (2009)
Boundary Element Method was used in the stress analysis of unidirectional composite laminate. The location of the maximum stress around the circumference of the central bore at fiber orientation of 0o and 90o respectively was determined. Crack would most likely initiate and propagate from these high stress regions. Defense hole was introduced in composite laminates and its effect of crack tip shielding was analysed. The distance of defense hole from the crack tip was varied and it was noticed that as it was located further away, it creates a crack tip shielding effect. The size of the defense was also varied and it was found that a large hole produces a crack tip enhancement effect.